Novel isobavachalcone derivatives induce apoptosis and necroptosis in human non-small cell lung cancer H1975 cells - Jie Chen; Long Zhao; Meng-Fan Xu; Di Huang; Xiao-Long Sun; Yu-Xin Zhang; Hong-Mei Li; Cheng-Zhu Wu (Taylor & Francis Group, 2024)
AbstractIn this study, seventeen isobavachalcone (IBC) derivatives (1-17) were synthesised, and evaluated for their cytotoxic activity against three human lung cancer cell lines. Among these derivatives, compound 16 displayed the most potent cytotoxic activity against H1975 and A549 cells, with IC50 values of 4.35 and 14.21 μM, respectively. Compared with IBC, compound 16 exhibited up to 4.11-fold enhancement of cytotoxic activity on human non-small cell lung cancer H1975 cells. In addition, we found that compound 16 suppressed H1975 cells via inducing apoptosis and necroptosis. The initial mechanism of compound 16 induced cell death in H1975 cells involves the increasing of Bax/Bcl-2 ratio and Cyt C protein level, down-regulating of Akt protein level, and cleaving caspase-9 and -3 induced apoptosis; the up-regulation of RIP3, p-RIP3, MLKL, and p-MLKL levels induced necroptosis. Moreover, compound 16 also caused mitochondrial dysfunction, thereby decreasing cellular ATP levels, and resulting in excessive reactive oxygen species (ROS) accumulation.